The Evaluation of Lubricants Performances in Light- and Heavy-Duty Diesel Engines in The Application of Biodiesel (B20). - Hanifuddin Hanifuddin; Milda Fibria; Catur Y. Respatiningsih; Setyo Widodo; Maymuchar Maymuchar (Testing Center for Oil and Gas LEMIGAS, 2020)
The use of biodiesel as fuel in light- and heavy-diesel engine vehicles in general will negatively affects the lubricant performance. the changes in lubricants properties during the use of B20 were investigated. Two type of vehicles engines were used, namely heavy duty and light duty diesel engines. The road test wascarried out until 40,000 km, while the lubricant was drained and analysed only for 10,000 km of distances. The laboratory test was conducted to observe both fresh and used lubricants. The results show that the biodiesel dilutions were less than 2% both in light- and heavy-duty diesel engines. The kinematic viscositiesof 4 samples of used lubricants in light-duty diesel engine were decreased in the ranges of 0.58 – 7.5%, while in heavy-duty diesel engines were 4.66-16.04% from the initial values. The decreasing of TBNs were less than 14% in light-duty diesel engine and fewer than 16% in heavy-duty diesel engine fuelled by biodiesel (B20). Meanwhile, the acidity of used engine oil was increased until 173% for light-duty diesel engine and 63% heavy-duty diesel engine compare to the initial values. The results show that the metal additives decreased while wear metal increased. According to this study, the increasing of wear metal (copper) in the used lubricants were less than 23% in light-duty diesel engine and lower than 26% in heavy-duty diesel engine fuelled by biodiesel (B20). Meanwhile, the lead contents of used engine oil were increased to 3.2 ppm in heavy-duty diesel engine and was not detected in light-duty diesel engine. After all, this work found that the lubricants exhibit good performances in the light- and heavy-duty diesel engines fuelled by B20. The changes of some critical properties were still in the acceptable values regarding to the specification as required in the SNI-7069-5 (2021).